2012
DOI: 10.1097/sla.0b013e3182444231
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinoembryonic Antigen Level in Pancreatic Juice and Mural Nodule Size Are Predictors of Malignancy for Branch Duct Type Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: We identified 2 useful predictive factors for malignancy in branch duct type IPMN; a mural nodule size >5 mm and a CEA level in the pancreatic juice obtained by preoperative ERP >30 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 20 publications
7
113
1
1
Order By: Relevance
“…In addition to the differences in various CT-based parameters between patients with benign and malignant IPMN, this study has also revealed higher CA 19-9 levels in the malignant cases, in agreement with previous studies [17,[29][30][31] . However, the wide overlap in CA 19-9 levels between the groups does not allow for a clear discrimination based on this parameters.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to the differences in various CT-based parameters between patients with benign and malignant IPMN, this study has also revealed higher CA 19-9 levels in the malignant cases, in agreement with previous studies [17,[29][30][31] . However, the wide overlap in CA 19-9 levels between the groups does not allow for a clear discrimination based on this parameters.…”
Section: Discussionsupporting
confidence: 79%
“…Additional factors have been found to be predictive of malignancy in these 32 In contrast, NLR is a less invasive method of evaluating the malignancy. The serum concentration of both CEA and CA19-9 was found to specifically correlate with IPMC.…”
Section: Discussionmentioning
confidence: 87%
“…1). Of these studies, 33 investigated mural nodules5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 21 examined dilatation of the main pancreatic duct (MPD)7 9, 15 16, 18 21, 23 26, 27 30, 32 36, 38, 39, 40, 41, 42, 43, 44, 45, 46, 21 analysed cyst size5 7, 8, 9 14, 15 18, 20 23, 25 27, 28 31, 36 38, 40 41, 43 47, 48, 49, 17 assessed CA19‐9 increase…”
Section: Resultsmentioning
confidence: 99%